Pengaruh Fasilitas, Keamanan, dan Pelayanan Kantor Syahbandar terhadap Kepuasan Nelayan di Pelabuhan Perikanan Pantai Tegalsari Kota Tegal - Arjun Andi Gunawan (Indonesian Maritime Researchers and Lecturers, 2025)
This study aims to analyze the impact of facilities, security, and services of the Syahbandar office on the satisfaction of fishermen at the Pantai Fishing Port (PPP) Tegalsari, Tegal City. The research method used is a quantitative approach with an associative model, where data is collected through a questionnaire distributed to 100 fishermen operating at PPP Tegalsari. Data analysis is performed using SPSS version 26 with validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that, simultaneously, the variables of facilities, security, and services have a positive and significant impact on fishermen’s satisfaction. Partially, the service variable has the most dominant influence on fishermen’s satisfaction compared to the facilities and security variables. This indicates that improving the quality of services at the Syahbandar office, providing adequate port facilities, and ensuring security at the port are key factors in creating fishermen’s satisfaction. This study is expected to provide input for port managers to enhance public service quality in the fisheries sector and promote policies that better address the needs and comfort of fishermen in their activities at the port.